Descriptions of three congeneric species of chewing lice of the Oxylipeurus-complex (Insecta: Phthiraptera: Philopteridae) from the turkey, Meleagris gallopavo, including a new genus and a new species - Gustafsson, Daniel R.; Zou, Fasheng (Zootaxa, 2020)
The lice of the Oxylipeurus-complex parasitising the turkey, Meleagris gallopavo, belong to a previously undescribed genus. In this paper, we describe this genus as Valimia new genus, redescribe two of its species: Lipeurus polytrapezius Burmeister, 1838 and Oxylipeurus corpulentus Clay, 1938, and describe the new species Valimia necopinata, discovered during our examination of samples of the two known species. This occurrence represents the first record of three congeneric species of chewing lice parasitising the same host individual.